Terapia nutricional enteral intermitente : interrupção diurna ou noturna? : estudo clínico randomizado - Pegoraro, Vanessa Alvarenga (2014)
Introduction: Regardless of continuous or intermittent administration in the Intensive Care Unit (ICU) patients usually receive their nutritional requirements calculated for enteral nutrition therapy (ENT) in less than planned volume, hindering their recovery. Thus, the interruption of scheduled shift ENT in performing daily routine activities of these units can contribute to reduce this deficit. Objectives: To assess the period, day or night, the interruption in the administration of enteral nutritional therapy in critically ill patients is more effective to ensure the calculated requirements. Methods: clinical, prospective , randomized study of quantitative approach in critically ill patients hospitalized to a general ICU . Patients over 18 years old were included in the exclusive use of ENT, observed in the first five days of diet. Patients in the act of nomination of ENT were randomized into two groups: Group I (18 hours ENT infusion – break of 6 hours in the period of 8 a.m. to 2 p.m.) and Group II (18 hours ENT infusion - break of 6 hours in the period of 2 a.m. to 8 a.m.). Among the groups the following variables were compared: sex, age, Apache II, ASG, weight, calorie needs, protein, diet prescribed volumes and infused. The quantitative variables were represented by medium-sized and standard deviation. The normality of the data by the Kolmogorov-Smirnov test and its homogeneity by Levene's test. Data analysis was performed by testing analysis of variance (ANOVA) and Tukey test Post Hoc. For categorical variables, the Chi-square test of Mantel-Haenszel or Fisher's Exact Test. We used the program SPSS version 18.0 (α = 5%). Results: the demographics data assessed were similar between the two groups. The assessment of severity using APACHE II showed similar groups (p = 0.168). In nutritional evaluation by ASG, none of the patients of both groups was ASG-A, ASG-B, 66.7% in Group I and 86.7% in Group II, ASG-C 33.3% and 13.3%, respectively, in groups I and II (p = 0.389). There were average weight identical in both groups (p = 0.978). Comparing the volume infused > 60% between the groups, in the Group I the infusion of diet was 66.7% versus 53.3% in Group II (p = 0.463). And, as for achieving the goals of NC until the 3rd day of infusion, group I obtained 13.3% compared with 6.7% in Group II (p = 0.549). And, the achieving of the NP in the same period, was in Group I compared to group II (20.0% vs. 6.7%, p = 0.290). Conclusion: Based on the results, we can conclude that the needs of enteral nutrition therapy calculated in critical patient are affected in a similar manner for both daytime and nighttime interruption.